PPARs: Protectors or Opponents of Myocardial Function? - Christine J. Pol; Melissa Lieu; Konstantinos Drosatos (PPAR Research)
Over 5 million people in the United States suffer from the complications of heart failure (HF), which is a rapidly expanding health complication. Disorders that contribute to HF include ischemic cardiac disease, cardiomyopathies, and hypertension. Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear receptor family. There are three PPAR isoforms: PPARα, PPARγ, and PPARδ. They can be activated by endogenous ligands, such as fatty acids, as well as by pharmacologic agents. Activators of PPARs are used for treating several metabolic complications, such as diabetes and hyperlipidemia that are directly or indirectly associated with HF. However, some of these drugs have adverse effects that compromise cardiac function. This review article aims to summarize the current basic and clinical research findings of the beneficial or detrimental effects of PPAR biology on myocardial function.